2018
DOI: 10.1088/1674-1056/27/8/084211
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 saturable absorber prepared by chemical vapor deposition method for nonlinear control in Q-switching fiber laser

Abstract: Due to the remarkable carrier mobility and nonlinear characteristic, MoS 2 is considered to be a powerful competitor as an effective optical modulated material in fiber lasers. In this paper, the MoS 2 films are prepared by the chemical vapor deposition method to guarantee the high quality of the crystal lattice and uniform thickness. The transfer of the films to microfiber and the operation of gold plated films ensure there is no heat-resistant damage and anti-oxidation. The modulation depth of the prepared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…However, very recently, it was demonstrated that the absorbance of ML-MoS 2 in the sub-bandgap region can be very large (e.g., 3% at 950 nm), possibly due to impurities, defects and edge states [12][13][14][15] . This phenomenon has attracted significant interest in pushing the applications of MoS 2 and other TMDs in the technologically important NIR region and beyond, such as infrared detectors [16][17][18] and saturable absorbers 6,[19][20][21][22][23][24][25][26][27][28] at the telecommunication wavelength range of~1.5 µm and the mid-infrared wavelength region. To better understand these intriguing applications, it is of high importance to study the optical properties and the carrier relaxation dynamics of TMDs in the sub-bandgap region, which can fully extend the applications of TMDs beyond their bandgap limitation.…”
Section: Introductionmentioning
confidence: 99%
“…However, very recently, it was demonstrated that the absorbance of ML-MoS 2 in the sub-bandgap region can be very large (e.g., 3% at 950 nm), possibly due to impurities, defects and edge states [12][13][14][15] . This phenomenon has attracted significant interest in pushing the applications of MoS 2 and other TMDs in the technologically important NIR region and beyond, such as infrared detectors [16][17][18] and saturable absorbers 6,[19][20][21][22][23][24][25][26][27][28] at the telecommunication wavelength range of~1.5 µm and the mid-infrared wavelength region. To better understand these intriguing applications, it is of high importance to study the optical properties and the carrier relaxation dynamics of TMDs in the sub-bandgap region, which can fully extend the applications of TMDs beyond their bandgap limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Passively Q-switched fiber lasers (QSFL), which are generated by Q-factor modulation or intracavity loss regulation, have attracted much attention because of their intrinsic advantages of high energy, alignment-free structure, compactness, and high stability [1][2][3][4]. Up to now, QSFLs have been widely applied in medicine, industrial material processing, fiber-optical sensing, and optical communication [5][6][7][8][9][10][11][12][13][14][15][16]; but they can also be used as an ideal platform for investigating the dynamic evolution of solitons and saturated absorption of nanomaterials [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the band gap structure of TMDs, which has obvious changes in gap value and indirect-to-direct transition as the thickness decreases, results in some unique properties such as high third-order nonlinear and ultrafast relaxation systems. As the representative of TMDs, molybdenum disulfide (MoS 2 ) has been widely concerned in optical nonlinearity [28][29][30]. It has been reported that the MoS 2 nanosheet exhibits a remarkable saturated absorption at 800 nm, which is better than that of graphene [31,32].…”
Section: Introductionmentioning
confidence: 99%